2022
DOI: 10.1038/s41598-022-10128-9
|View full text |Cite
|
Sign up to set email alerts
|

Smart pooling: AI-powered COVID-19 informative group testing

Abstract: Massive molecular testing for COVID-19 has been pointed out as fundamental to moderate the spread of the pandemic. Pooling methods can enhance testing efficiency, but they are viable only at low incidences of the disease. We propose Smart Pooling, a machine learning method that uses clinical and sociodemographic data from patients to increase the efficiency of informed Dorfman testing for COVID-19 by arranging samples into all-negative pools. To do this, we ran an automated method to train numerous machine lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The partition of the high and low risk group are defined through a machine learning algorithms (Escobar et al, 2022; Park et al, 2022). The classifier allows optimizing each strategy for each group reducing the overall number of tests applied and costs.…”
Section: Introductionmentioning
confidence: 99%
“…The partition of the high and low risk group are defined through a machine learning algorithms (Escobar et al, 2022; Park et al, 2022). The classifier allows optimizing each strategy for each group reducing the overall number of tests applied and costs.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, “smart pooling” was proposed by Escobar et al . to overcome the problems of prevalence variability and failure in using group testing in settings with high prevalence 15 . Smart pooling uses a priori information about the patient to calculate the probability of an individual to be positive, based on the individual’s clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…Escobar et al . showed that in an area with a COVID-19 prevalence of 50%, smart pooling still could be 6% more efficient than conventional testing 15 . In another study, Deckerts et al .…”
Section: Introductionmentioning
confidence: 99%
“…11 However, NGS requires labor-intensive protocols, expensive sequencing platforms, and a high-power computing device for data analysis, which makes it difficult to scale up, especially in resource-limited regions. Machine learning-powered pooling test 12 and digital PCR technology 13 have been studied to improve the efficiency and sensitivity of Dorfman group testing even during high disease prevalence, but these methods still require retest steps. Recently, our group developed a pooled assay for a largescale screening named Unique Barcoded Primer-Assisted Sample-Specific Pooled Testing (Uni-Pool), which can realize sample-specific testing of pooled samples without retesting.…”
mentioning
confidence: 99%
“… 11 However, NGS requires labor-intensive protocols, expensive sequencing platforms, and a high-power computing device for data analysis, which makes it difficult to scale up, especially in resource-limited regions. Machine learning-powered pooling test 12 and digital PCR technology 13 have been studied to improve the efficiency and sensitivity of Dorfman group testing even during high disease prevalence, but these methods still require retest steps.…”
mentioning
confidence: 99%